Pengembangan Aplikasi Konversi Representasi Not Balok Ke Not Angka Untuk Paduan Suara Campur - Lukas Chrisantyo; Rudy Hartanto; Lukito Edy Nugroho (Universitas Kristen Duta Wacana, 2012)
Beam notation is a notation that is officially used in the whole world as an intermediary to do musical communication. In Indonesia, notation that is more absorbed and mostly easy to learn autodidactly is numbered notation, while beam notation is more difficult to learn and tend to be avioded. Traditionally, beam notation can be converted to numbered notation by fully relying on human skills and abilities. It is obvious that the conversion process would require much time and energy. Therefore, a new conversion application is developed to cope the conversion from beam notation into numbered notation specally for mixed choir, with representated in a XML file called MusicXML. MusicXML is a representation of beam notation that are more easily to be compressed and has a universal characteristic, can be opened in a wide range of applications. The purpose of this research was to design a fast, reliable and accurate application to convert beam notation into numbered notation for mixed choir which consist of multiple voice parts, according to the prevailing theory of music. Kata-kunci: rekayasa perangkat lunak, konversi notasi musik, MusicXML